Data Mining Design In Teacher Teaching Assessment Based On Student Satisfaction Index - Seriani Loi; Jani Sirat; Elsa Naibaho (Geviva Publisher, 2022)
Teacher performance appraisal is an analytical process in order to produce good teaching The process of assessing teacher performance at SMP Kartika Pematangsiantar is not so detailed (detailed). With the non-detailed assessment, it is feared that there will be a subjective assessment (based on personal interests), which can cause social jealousy for teachers who do not accept achievement. In the assessment of teacher teaching, data on student satisfaction with the teacher is needed. In collecting data using a questionnaire and the variables used in this research there are 4, namely discipline, teaching quality, behavior, and social relations. This study aims to assist the school in improving the performance of teachers, especially in the way of teaching teachers based on student satisfaction by using the C4.5 . method.